Analisis Penggunaan Bahasa Slang pada Masyarakat Baduy Luar - Annisa Dwi Oktaviyani; Silva Azahra; Melawati Melawati; Eneng Liah Khoiriyah; Iim Khairunnisa (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This study uses a descriptive qualitative research method to analyze the variation of slang used by the Baduy local community, Desa Kanekes. The data collected is a data primer, which is collected through fieldwork and data collection through questionnaires. The research also uses a survey method to gather information from 10 local residents, focusing on the use of slang and language in their daily lives. The results show that the majority of residents use slang in their daily lives, with some using it in their daily conversations. The study also identifies three slang variations: "On the Way" (OTW), "Lebay", and "COD". OTW is a slang variation that refers to the current time of the conversation, while "Lebay" is a slang variation that refers to the current time of the conversation. COD is a slang variation that refers to the amount of money paid for goods delivered, and it is used by some locals for online transactions. The study highlights the importance of understanding and utilizing slang in the local community.